Development and validation of the Approach-Iron Skill Test for use in golf - Robertson, S. J.; Burnett, A. F.; Newton, R. U. (European Journal of Sport Science, 2013)
The primary aim of this study was to develop and validate a golf-specific approach-iron test for use with elite and high-level amateur golfers. Elite (n=26) and high-level amateur (n=23) golfers were recruited for this study. The `Approach-Iron Skill Test` requires players to hit a total of 27 shots. Specifically, three shots are hit at each of nine targets on a specially constructed driving range in a randomised order. A real-time launch monitor positioned behind the player, measured the carry distance for each of these shots. A scoring system was developed based on the percentage error index of each shot, meaning that 81 points was the maximum score possible (with a maximum of three points per shot). Two rounds of the test were performed. For both rounds of the test, elite-level golfers scored significantly higher than their high-level amateur counterparts (56.3±5.6 and 58.5±4.6 points versus 46.0±6.3 and 46.1±6.7 points, respectively) (P<0.05). For both elite and high-level players, 95% limits of agreement statistics also indicated that the test showed good test-retest reliability (2.1±7.9 and 0.2±10.8, respectively). Due to the clinimetric properties of the test, we conclude that the Approach-Iron Skill Test is suitable for further examination with the players examined in this study.